The Effectiveness Of “Numbered Heads Together” Cooperative Learning Model In Nahwu Learning Outcomes - Ifa Rodifah Nur; Zehra Oran; Fitri Setyo Rini; Siti Nur Resky Ahmalia Putri; Ahmad Kali Akbar (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
The learning model is an essential element in the learning process. Many studies state that the Numbered Heads Together is a learning model that has proven effective in increasing student interest and learning outcomes in various materials. However, not much research has revealed the effectiveness of NHT in language learning, especially in Arabic. Therefore, the researchers want to explore the efficacy of the NHT learning model in improving Arabic learning outcomes on nahwu material. This study aims to explain the effectiveness of using the Numbered Heads Together cooperative learning model in enhancing learning outcomes of nahwu material. The research design used was the Experiment posttest-only control design. The sample divided into two classes was all second-grade students of KMI PP Khadimul Ummah Riau. The data collection method used tests, while the data analysis method used the t-test and SPSS 16. The results of the data analysis in this study were: (1) posttest on experimental class students with minimum value of 65, maximum value of 100, and mean of 83.00. The minimum posttest results for control class students were 53, the top score was 90, and the mean was 74.26. (2) The results of this study indicated that Sig. (2-tailed) from the Mann-Whitney Test was 0.003 <0.05. From these data, NHT cooperative learning significantly influences the learning outcomes of second-grade students at Khodimul Ummah Riau Islamic Boarding School.